Association of prenatal alcohol exposure and prenatal depressive symptoms with offspring hair cortisol in childhood and adolescence - Plank, Anne-Christine; Panaseth-Gehle, Kerstin; Gerlach, Jennifer; Mestermann, Stefan; Fasching, Peter A.; Beckmann, Matthias W.; Kratz, Oliver; Moll, Gunther H.; Lenz, Bernd; Kornhuber, Johannes; Eichler, Anna (BMC psychiatry, 2025)
Prenatal alcohol exposure (PAE) and maternal depressive symptoms are associated with hypothalamic-pituitary-adrenal (HPA) axis alterations in the offspring. The present study investigated long-term associations of both risk factors on the offspring’s hair cortisol concentration (HCC) in childhood and adolescence.
Gesehen am 09.12.2025